2003
DOI: 10.1002/tt.3020100102
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antiwear coatings deposited by the pvd process

Abstract: The tribological properties of various PVD‐deposited coatings (vacuum arc method) have been tested, both single‐layer coatings (TiN, CrN, Ti(C,N), and Cr(C,N)) and multilayer coatings (Cr(C,N)/CrN/Cr and CR(C,N)/(CrN+Cr2N)/CrN/Cr). An unlubricated ball‐on‐disc tribosystem was used in which an Al2O3 ball is pressed against a coated steel disc rotating in the horizontal plane. A novelty of the method is the removal of wear debris from the contact zone using a draught of dry argon. This improves the repeatability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…When one of the mating materials (coating) is much harder than the other one (steel), there is a reduction in the tendency to adhesive bonding, friction, hence scuffing. The same occurrence was observed when testing the coated spur gears [5]. Both phenomena also led to the reduction in the oil temperature in case of the coated wheel during the laboratory stage of the experiment (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…When one of the mating materials (coating) is much harder than the other one (steel), there is a reduction in the tendency to adhesive bonding, friction, hence scuffing. The same occurrence was observed when testing the coated spur gears [5]. Both phenomena also led to the reduction in the oil temperature in case of the coated wheel during the laboratory stage of the experiment (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Shot peening is a new technology that is categorized into: laser shock peening [8], ultrasonic shot peening [9], fine particle peening [10], and water cavitation peening [11]. Gear surface coating modification commonly utilizes TiN coating [12], MoS2/Ti membrane [13], and phosphate coating. Lv Y. et al investigated the effect of shot peening modification and radar surface processing parameters on the fatigue property of 20CrMnTi gear; results showed that the fatigue lifetimes of the LSMSSP gears are grain determined by the retained austenite and surface roughness [5].…”
Section: Introduction mentioning
confidence: 99%